Defining failure of endoluminal biliary drainage in the era of endoscopic ultrasound and lumen apposing metal stents - Ali, Faisal S; Guha, Sushovan (World journal of gastroenterology : WJG, 2024)
The role of endoscopy in pathologies of the bile duct and gallbladder has seen notable advancements over the past two decades. With advancements in stent technology, such as the development of lumen-apposing metal stents, and adoption of endoscopic ultrasound and electrosurgical principles in therapeutic endoscopy, what was once considered endoscopic failure has transformed into failure of an approach that could be salvaged by a second- or third-line endoscopic strategy. Incorporation of these advancements in routine patient care will require formal training and multidisciplinary acceptance of established techniques and collaboration for advancement of experimental techniques to generate robust evidence that can be utilized to serve patients to the best of our ability.